2016
DOI: 10.1371/journal.pone.0160076
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator Foraging Adaptation and Coexistence of Competing Plants

Abstract: We use the optimal foraging theory to study coexistence between two plant species and a generalist pollinator. We compare conditions for plant coexistence for non-adaptive vs. adaptive pollinators that adjust their foraging strategy to maximize fitness. When pollinators have fixed preferences, we show that plant coexistence typically requires both weak competition between plants for resources (e.g., space or nutrients) and pollinator preferences that are not too biased in favour of either plant. We also show h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…There has been recent theoretical interest in coexistence of mutualists that compete for shared commodities (Lee and Inouye , Benadi et al. , , Song and Feldman , Benadi , Revilla and Křivan ). These models, however, do not yield clear criteria for competitive exclusion, as R * and P * theories do for other consumer–resource interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There has been recent theoretical interest in coexistence of mutualists that compete for shared commodities (Lee and Inouye , Benadi et al. , , Song and Feldman , Benadi , Revilla and Křivan ). These models, however, do not yield clear criteria for competitive exclusion, as R * and P * theories do for other consumer–resource interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the vast majority of mutualism models do not mechanistically consider competition for mutualistic commodities (Johnson and Amarasekare 2013), either because they focus on tightly coupled pairwise mutualisms in which interspecific competition is irrelevant, or because commodities are implicitly modeled such that they do not constitute limiting factors. There has been recent theoretical interest in coexistence of mutualists that compete for shared commodities (Lee and Inouye 2010, Benadi et al 2012, Song and Feldman 2014, Benadi 2015, Revilla and K rivan 2016. These models, however, do not yield clear criteria for competitive exclusion, as R* and P* theories do for other consumerresource interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the juvenile is not a full specialist, that is the two plant species share a predator (herbivore), then they are involved in apparent competition (Holt ). Similarly, even though pollen dilution may happen, observations suggest that pollinator sharing may create dominant facilitative effects among plant species (Tur et al ). Therefore, apparent mutualism among plant species is possible, when the adult stage is not a full specialist.…”
Section: Introductionmentioning
confidence: 99%
“…arXiv mainly holds studies in physical and 'quantitative' science, although some of the studies mentioned above can be found there [1][2][3] . A significant feature of arXiv is that articles can be revised and updated, something that is difficult to achieve in formal literature.…”
mentioning
confidence: 99%